The influence of n-3 polyunsaturated fatty acids and very low calorie diet during a short-term weight reducing regimen on weight loss and serum fatty acid composition in severely obese women - Kunesová, M; Braunerová, R; Hlavatý, P; Tvrzická, E; Stanková, B; Skrha, J; Hilgertová, J; Hill, M; Kopecký, J; Wagenknecht, M; Hainer, V; Matoulek, M; et al. (Physiological research, 2006)
Polyunsaturated fatty acids of n-3 series (n-3 PUFA) were shown to increase basal fat oxidation in humans. The aim of the study was to compare the effect of n-3 PUFA added to a very low calorie diet (VLCD), with VLCD only during three-week inpatient weight reduction. Twenty severely obese women were randomly assigned to VLCD with n-3 PUFA or with placebo. Fatty acids in serum lipid fractions were quantified by gas chromatography. Differences between the groups were determined using ANOVA. Higher weight (7.55+/-1.77 vs. 6.07+/-2.16 kg, NS), BMI (2.82+/-0.62 vs. 2.22+/-0.74, p<0.05) and hip circumference losses (4.8+/-1.81 vs. 2.5+/-2.51 cm, p<0.05) were found in the n-3 group as compared to the control group. Significantly higher increase in beta-hydroxybutyrate was found in the n-3 group showing higher ketogenesis and possible higher fatty acid oxidation. The increase in beta-hydroxybutyrate significantly correlated with the increase in serum phospholipid arachidonic acid (20:4n-6; r = 0.91, p<0.001). In the n-3 group significantly higher increase was found in n-3 PUFA (eicosapentaenoic acid, 20:5n-3, docosahexaenoic acid, 22:6n-3) in triglycerides and phospholipids. The significant decrease of palmitoleic acid (16:1n-7) and vaccenic acid (18:1n-7) in triglycerides probably reflected lower lipogenesis. A significant negative correlation between BMI change and phospholipid docosahexaenoic acid change was found (r = -0.595, p<0.008). The results suggest that long chain n-3 PUFA enhance weight loss in obese females treated by VLCD. Docosahexaenoate (22:6n-3) seems to be the active component.
Keywords: Caloric Restriction; Fatty Acids, Omega-3; Female; Oleic Acids; Fatty Acids, Monounsaturated; ženské pohlaví; kyseliny dokosahexaenové; triglyceridy; Diet, Reducing; Dietary Supplements; kyselina eikosapentaenová; Obesity; Triglycerides; lidé; kyseliny olejové; fosfolipidy; Eicosapentaenoic Acid; potravní doplňky; Middle Aged; omega-3 mastné kyseliny; Weight Loss; obezita; Phospholipids; redukční dieta; hmotnostní úbytek; kyseliny mastné mononenasycené; lidé středního věku; 3-Hydroxybutyric Acid; kyselina 3-hydroxymáselná; kalorická restrikce; Docosahexaenoic Acids; Humans